2021
DOI: 10.1088/1742-6596/1808/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ARCS Based Economic E-Book to Improve Learning Motivation and Learning Outcomes

Abstract: This study aims to test the effectiveness of ARCS-based economic e-book media to improve learning motivation and learner outcomes. This is back grounded by the lack of motivation of students’ learning in following the economic learning process so that the results of learning students in economic learning become not maximal. With good learning motivation, it will boil down to achieving good learning outcomes as well. The data collected in this study is motivational learning data collected through questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Consistent with other research, e-books have been demonstrated to enhance student motivation and improve the efficiency and efficacy of teaching and learning practices (Algani et al, 2021). Furthermore, what was discovered in a study conducted by other study indicated that the implementation of ARCS-based economic e-book media yielded a positive impact on enhancing students' learning motivation and academic achievements (Saputri et al, 2021). The study's findings were derived from an analysis of data obtained from pre-test and post-test measurements and N-Gain calculations conducted in both the experimental and control classes.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with other research, e-books have been demonstrated to enhance student motivation and improve the efficiency and efficacy of teaching and learning practices (Algani et al, 2021). Furthermore, what was discovered in a study conducted by other study indicated that the implementation of ARCS-based economic e-book media yielded a positive impact on enhancing students' learning motivation and academic achievements (Saputri et al, 2021). The study's findings were derived from an analysis of data obtained from pre-test and post-test measurements and N-Gain calculations conducted in both the experimental and control classes.…”
Section: Discussionmentioning
confidence: 98%